NIMG-24. GLYCINE AND GLUTAMINE BY MR SPECTROSCOPY ARE IMAGING BIOMARKERS OF GLIOMA AGGRESSIVENESS. (9th November 2020) - Choi, Changho; Askari, Pegah; Daoud, Elena; Hatanpaa, Kimmo; Raisanen, Jack; Lewis, Cheryl; Levy, Michael; Patel, Toral; Pan, Edward; Mickey, Bruce; Maher, Elizabeth
Abstract: Cancers reprogram their metabolism and the resulting alterations in metabolite concentrations may be closely related to the clinical behavior of the tumors. We evaluated glycine, glutamine and 2-hydroxyglutarate (2HG) in 16 adult subjects with glioblastomas (9 male and 7 female; age 43-64 years, median 58) noninvasively using proton magnetic resonance spectroscopy and examined their association with the cell proliferation rate (MIB-1 labeling index) and overall survival. MRS was acquired using point-resolved spectroscopy (PRESS TE 97ms) at 3T. Metabolite levels were quantified with reference to water. The concentrations of glycine and glutamine were both positively correlated with MIB-1 (p=.002 and .0008 respectively). The sum of glycine and glutamine levels showed stronger association with MIB-1 (p< .0001). In the Kaplan-Meier overall survival analysis, the median survival was significantly shorter in patients with glycine levels higher than 2.3 mM than those with concentrations less than 2.3 mM. For glutamine, the patients with higher than 5.7 mM showed association with poor survival. The log-rank p value was substantially smaller in glutamine compared to glycine (p=.008 vs .04). The sum of glycine and glutamine levels showed stronger association with overall survival. 2HG level greater than 1 mM was associated with long survival, which was as expected since elevation of 2HG represents IDH mutant tumors and IDH mutation carries favorable prognosis. Given the association of low 2HG with poor survival, we tested metabolic ratios to 2HG, in which 2HG estimates < 1 mM were put as 1 mM. The glycine/2HG, glutamine/2HG, and (glycine+glutamine)/2HG showed stronger association with overall survival, compared to glycine, glutamine, and glycine+glutamine. Our data suggested that increased metabolism of glycine and glutamine is closely associated with rapid cell proliferation and poor clinical outcome, suggesting the metabolites as an MRS imaging biomarker of glioma aggressiveness.